Texture Changes and Storage of Rice - Perez, Consuelo M.; Juliano, Bienvenido O. (Wiley, 1981)
Monthly texture assessments of seven milled rices, differing in amylose content and stored at 28–30°C, verified that three months was the minimum storage period for major changes to occur in hardness of cooked rice, gel consistency, and amylograph viscosity values. Therefore, texture measurements should be done on samples aged at least three months after harvest. Texture changes tend to be greatest for high‐amylose rice with hard gel consistency and least for waxy rice. Free fatty acids were highest in stored, waxy, milled rice. Storage under nitrogen instead of air had a slight retarding effect on storage changes of five rices in another study. Surface defatting with petroleum ether had little effect on storage change in cooked rice hardness and stickiness, but reduced the changes in gel consistency and amylograph setback and consistency.